Поставьте на черное: [роман] / Лев Гурский - Гурский Лев Аркадьевич (Д. Д. Д., 1999)
Экземпляры: АБ (20190701) / Инвентарный номер: 32048 / Цена: 26.50 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Г 95 / ББК: 84(2Рос=Рус)6-4